Growth of 2D Mesoporous Polyaniline with Controlled Pore Structures on Ultrathin MoS2 Nanosheets by Block Copolymer Self-Assembly in Solution - Tian, Hao; Zhu, Shuyan; Xu, Fugui; Mao, Wenting; Wei, Hao; Mai, Yiyong; Feng, Xinliang (ACS Applied Materials and Interfaces, 2017)
The development of versatile strategies toward two-dimensional (2D) porous nanocomposites with tunable pore structures draws immense scientific attention in view of their attractive physiochemical properties and a wide range of promising applications. This paper describes a self-assembly approach for the directed growth of mesoporous polyaniline (PANi) with tunable pore structures and sizes on ultrathin freestanding MoS2 nanosheets in solution, which produces 2D mesoporous PANi/MoS2 nanocomposites. The strategy employs spherical and cylindrical micelles, which are formed by the controlled solution self-assembly of block copolymers, as the soft templates for the construction of well-defined spherical and cylindrical mesopores in the 2D PANi/MoS2 nanocomposites, respectively. With potential applications as supercapacitor electrode materials, the resultant 2D composites show excellent capacitive performance with a maximum capacitance of 500 F g-1 at a current density of 0.5 A g-1, good rate performance, as well as outstanding stability for charge-discharge cycling. Moreover, the 2D mesoporous nanocomposites offer an opportunity for the study on the influence of different pore structures on their capacitive performance, which helps to understand the pore structure-property relationship of 2D porous electrode materials and to achieve their electrochemical performance control.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D materials; block copolymer; mesoporous; pore structure; self-assembly